The Capstone ePortfolio in an Undergraduate Public Health Program: Accreditation, Assessment, and Audience - Harver, Andrew; Zuber, Pilar d.; Bastian, Heather (Frontiers in Public Health, 2019)
The Bachelor of Science in Public Health (BSPH) degree program at the University of North Carolina at Charlotte (UNC Charlotte) was launched in 2007, and was initially accredited by the Council on Education for Public Health in 2009. We admit approximately 40–45 students each fall to the upper division major, through a competitive admissions process. During the junior and senior years, BSPH majors complete a core set of required courses including internship; 18 credit hours of restricted electives; and any minor offered by the university (except public health). During 2014–2015, the Department of Public Health Sciences was one of five campus units supported by UNC General Administration to pilot the use of ePortfolios as a tool to help students integrate learning across the courses that make up the major. The pilot program continued for 2 additional years, to promote enduring faculty efforts. We subsequently outline the development and implementation of ePortfolio pedagogy in the BSPH program at UNC Charlotte, including preliminary assessment of outcomes the past 3 years. The adoption of ePortfolios has been instrumental in students' educational experiences for over 2 decades. The Association of American Colleges and Universities (AAC&U) has advocated that “ePortfolios allow faculty and other educational professionals to help students organize their learning; preserve the variety of forms in which their learning occurs; and reflect upon their learning.” We have learned that effective student ePortfolios do not arise in a vacuum. In collaboration with like-minded campus colleagues including those associated with the university's Communication Across the Curriculum program, we have encountered contributing forces related to the process of “collection, selection, and reflection” including intentional assignments that yield effective student artifacts; and authentic feedback to students through adoption and modification of the AAC&U VALUE rubrics. We conclude that internal and external forces drive the development of ePortfolio content; students embrace opportunities to document learning when those opportunities are structured; the development of the ePortfolio is relational—consistent with student attributes; and ePortfolios enable evidence-based approaches to meet accreditation demands, assessment needs, and workforce expectations.